2014
DOI: 10.1521/pedi_2014_28_131
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Borderline Personality Disorder Symptoms and Parenting of Adolescent Daughters

Abstract: Maternal borderline personality disorder (BPD) symptoms are associated with poorer parenting. However, most studies conducted are with young children. In the current study, the authors examined associations between maternal BPD symptoms and parenting in an urban community sample of 15- to 17-year-old girls (n = 1,598) and their biological mothers. Additionally, the authors tested the impact of adolescent temperament on these associations. Mothers reported on their own psychopathology and their daughters' tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 35 publications
2
43
2
Order By: Relevance
“…Likewise, Bridgett et al (2013) reported a negative association between better maternal behavioral SR and lower family cumulative risk, and Deater-Deckard et al (2012) reported a positive relation between better maternal behavioral SR and higher family SES. Zalewski et al (2014) also noted associations between poorer maternal emotional SR and lower educational attainment, a risk factor often included in cumulative risk indices (but, see Samuelson et al, 2012 who did not find significant relations between maternal emotional SR and educational attainment). Similar to the findings reported by Zalewski et al, Creed and colleagues (Creed, King, Hood, & McKenzie, 2009) reported a positive relation between better behavioral and emotional SR and more intense job seeking in a sample of unemployed Australian adults.…”
Section: Associations Between Parent and Child Self-regulationmentioning
confidence: 98%
“…Likewise, Bridgett et al (2013) reported a negative association between better maternal behavioral SR and lower family cumulative risk, and Deater-Deckard et al (2012) reported a positive relation between better maternal behavioral SR and higher family SES. Zalewski et al (2014) also noted associations between poorer maternal emotional SR and lower educational attainment, a risk factor often included in cumulative risk indices (but, see Samuelson et al, 2012 who did not find significant relations between maternal emotional SR and educational attainment). Similar to the findings reported by Zalewski et al, Creed and colleagues (Creed, King, Hood, & McKenzie, 2009) reported a positive relation between better behavioral and emotional SR and more intense job seeking in a sample of unemployed Australian adults.…”
Section: Associations Between Parent and Child Self-regulationmentioning
confidence: 98%
“…In particular, the latter feature is frequently found in those with borderline personality traits, and relate to alexithymia, a predictor of clinical severity and poor prognosis in ED patients (Speranza et al, 2007(Speranza et al, , 2011.. Although further longitudinal studies are needed, these couples of mothers and daughters with borderline/antisocial features may represent a risk factor for a more severe course of ED (Zalewski et al, 2014).…”
Section: Mothers' Temperament Clusters and Daughters' Featuresmentioning
confidence: 99%
“…Specifically, cognitively based regulatory processes, such as working memory, attention, cognitive flexibility, and/or inhibition, are linked to parenting behaviors such as intrusiveness (Cuevas et al, 2014), lower sensitivity (Chico et al, 2014; Gonzales, Jenkins, Steiner, & Fleming, 2012), and harsh parenting (Deater-Deckard, Wang, Chen, & Bell, 2012). Associations between general emotion dysregulation and parenting behaviors have also been demonstrated, including poor discipline implementation (Kim, Pears, Capaldi, & Owen, 2009), low emotional availability (Kim, Teti, & Cole, 2012), and harsh punishment (Zalewski et al, 2014). …”
mentioning
confidence: 99%